Optical Properties of Poly(2- thioacetate) Thin Films Prepared By Spin-Coating Method - AL-Malki, Ziyad T.; Hussein, Abdullah A.; AL-Fregi, Adel A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Poly(2-thioacetate) has been prepared and characterized by infrared spectroscopy (IR). A thin film of new Polythioacetate been prepared by spin-coating technique and its optical properties were studied . Transmittance measurements in the wavelength range (300-900 nm) were used to calculate the refractive index n and extinction coefficient k. The optical band gap Eg , optical conductivity σopt, electrical conductivity σe , real dielectric constant, complex dielectric constant, relaxation time τ and dissipation factor tan δ were determined. The analysis of the optical absorption data indicated that the optical band gap Eg was governed indirect transitions. According to Wemple and Didomenico method, the optical dispersion parameters Eo ( average excitation energy for electronic) and Ed( dispersion energy) were determined.
Keywords: Optical properties; Polythioacetate; Refractive index; optical energy gap